A realist evaluation of a training programme to enable experienced therapists to implement a complex rehabilitation intervention in a research setting - Howe, Louise (2024)
Background Our ageing population is living longer; many people live with comorbid conditions that affect their function, health, and quality of life. This population requires complex rehabilitation interventions, and large-scale randomised controlled trials (RCTs) are the preferred method of evaluating their effectiveness. The therapists delivering these interventions need training and support to ensure they provide a high-quality intervention with fidelity to the manual. Little has been reported in trial papers around training, which varies in terms of the type of training and the detail of documentation. There have been a number of multi-site RCTs of complex rehabilitation interventions that did not demonstrate positive results. It has been suggested that inconsistent intervention delivery or a lack of training may have contributed to the results. This PhD evaluates the training programme designed to support therapists in delivering a rehabilitation intervention for the Promoting Activity, Independence and Stability in Early Dementia (PrAISED) RCT.